Step
*
2
1
2
1
2
1
of Lemma
arctan-poly-approx-1
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. ∀x:ℝ. -(x^2) ≠ r1
3. x : {x:ℝ| r0 ≤ x} 
4. k : ℕ
5. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
6. (arctangent(x) - arctan-poly(x;k)) = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
7. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = r0_∫-x (-(x^2)^k + 1/r1 + x^2) dx
8. r0_∫-x (-(x^2)^k + 1/r1 + x^2) dx = (r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx)
⊢ |r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx| ≤ (x^(2 * k) + 3/r((2 * k) + 3))
BY
{ (Assert |r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx| = |r0_∫-x (x^2^k + 1/r1 + x^2) dx| BY
         ((GenConclTerm ⌜r0_∫-x (x^2^k + 1/r1 + x^2) dx⌝⋅ THENA Auto)
          THEN (RWO "rnexp-minus-one" 0 THEN Auto)
          THEN AutoSplit
          THEN (nRNorm 0 THEN Auto)
          THEN RWO  "rabs-rminus" 0
          THEN Auto)) }
1
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. ∀x:ℝ. -(x^2) ≠ r1
3. x : {x:ℝ| r0 ≤ x} 
4. k : ℕ
5. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
6. (arctangent(x) - arctan-poly(x;k)) = (arctangent(x) - r0_∫-x Σ{-(x^2)^i | 0≤i≤k} dx)
7. r0_∫-x (r1/r1 + x^2) - Σ{-(x^2)^i | 0≤i≤k} dx = r0_∫-x (-(x^2)^k + 1/r1 + x^2) dx
8. r0_∫-x (-(x^2)^k + 1/r1 + x^2) dx = (r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx)
9. |r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx| = |r0_∫-x (x^2^k + 1/r1 + x^2) dx|
⊢ |r(-1)^k + 1 * r0_∫-x (x^2^k + 1/r1 + x^2) dx| ≤ (x^(2 * k) + 3/r((2 * k) + 3))
Latex:
Latex:
1.  \mforall{}x:\mBbbR{}.  (r0  <  (r1  +  x\^{}2))
2.  \mforall{}x:\mBbbR{}.  -(x\^{}2)  \mneq{}  r1
3.  x  :  \{x:\mBbbR{}|  r0  \mleq{}  x\} 
4.  k  :  \mBbbN{}
5.  r0\_\mint{}\msupminus{}x  (r1/r1  +  x\^{}2)  -  \mSigma{}\{-(x\^{}2)\^{}i  |  0\mleq{}i\mleq{}k\}  dx  =  (arctangent(x)  -  r0\_\mint{}\msupminus{}x  \mSigma{}\{-(x\^{}2)\^{}i  |  0\mleq{}i\mleq{}k\}  dx)
6.  (arctangent(x)  -  arctan-poly(x;k))  =  (arctangent(x)  -  r0\_\mint{}\msupminus{}x  \mSigma{}\{-(x\^{}2)\^{}i  |  0\mleq{}i\mleq{}k\}  dx)
7.  r0\_\mint{}\msupminus{}x  (r1/r1  +  x\^{}2)  -  \mSigma{}\{-(x\^{}2)\^{}i  |  0\mleq{}i\mleq{}k\}  dx  =  r0\_\mint{}\msupminus{}x  (-(x\^{}2)\^{}k  +  1/r1  +  x\^{}2)  dx
8.  r0\_\mint{}\msupminus{}x  (-(x\^{}2)\^{}k  +  1/r1  +  x\^{}2)  dx  =  (r(-1)\^{}k  +  1  *  r0\_\mint{}\msupminus{}x  (x\^{}2\^{}k  +  1/r1  +  x\^{}2)  dx)
\mvdash{}  |r(-1)\^{}k  +  1  *  r0\_\mint{}\msupminus{}x  (x\^{}2\^{}k  +  1/r1  +  x\^{}2)  dx|  \mleq{}  (x\^{}(2  *  k)  +  3/r((2  *  k)  +  3))
By
Latex:
(Assert  |r(-1)\^{}k  +  1  *  r0\_\mint{}\msupminus{}x  (x\^{}2\^{}k  +  1/r1  +  x\^{}2)  dx|  =  |r0\_\mint{}\msupminus{}x  (x\^{}2\^{}k  +  1/r1  +  x\^{}2)  dx|  BY
              ((GenConclTerm  \mkleeneopen{}r0\_\mint{}\msupminus{}x  (x\^{}2\^{}k  +  1/r1  +  x\^{}2)  dx\mkleeneclose{}\mcdot{}  THENA  Auto)
                THEN  (RWO  "rnexp-minus-one"  0  THEN  Auto)
                THEN  AutoSplit
                THEN  (nRNorm  0  THEN  Auto)
                THEN  RWO    "rabs-rminus"  0
                THEN  Auto))
Home
Index